Changes in Factors Regulating Serum Sodium Homeostasis During Two Ultra-Endurance Mountain Races of Different Distances: 69km vs. 121km - Schenk, Kai; Rauch, Simon; Procter, Emily; Grasegger, Katharina; Mrakic-Sposta, Simona; Gatterer, Hannes (Frontiers in Physiology, 2021)
There is still limited knowledge about the risk factors triggering serum sodium aberrations during ultra-mountain marathon running of different distances. Twelve male participants (11 finishers) of the short (69 km, 4260 m elevation-gain) and 15 male participants (seven finishers) of the long (121 km, 7554 m elevation-gain) single-stage Südtirol Ultra Sky-Race took part in this investigation. Venous blood was drawn immediately before and after the race. Analyses included serum sodium concentration, copeptin (a stable marker for vasopressin), markers of inflammation, muscle damage and oxidative stress. Heart rate was measured during the race and race time was obtained from the race office. Prevalence of hypernatremia was 18% during the short run and 14% during the long run. No cases of hyponatremia were registered during the short run whereas its prevalence was 14% during the long run. Only during the short competition percent changes in serum sodium concentrations of the finishers were related to percent changes in body weight (r=-0.812, p=0.002), total time (r=-0.608, p=0.047) and training impulse (TRIMP) (r=-0.653, p=0.030). Data show a curvilinear (quadratic) relationship between percent changes in serum sodium concentration and body weight with race time when including all runners (short, long, finishers and non-finishers). The observed prevalence of hypo- and hypernatremia is comparable to literature reports, as is the relationship between serum sodium changes and race time, race intensity and body weight changes of the finishers of the short race. The curvilinear relationship indicates that there might be a turning point of changes in serum sodium and body weight changes after a race time of approximately 20 hours. This certainly deserves attention in future investigation.